Effect of active and passive techniques used in thromboembolic prophylaxis on venous flow velocity in the post-procedure period - Zsenák, István; Makai, Alexandra; Kiss, Gabriella; Faludi, Béla; Straub, Alexandra; Szilágyi, Brigitta; Velényi, Anita; Járomi, Melinda (Frontiers in Physiology, 2024)
Studies have shown that using mechanical thromboembolic prophylaxis methods speeds up venous flow and decreases stasis. These studies examine the post-intervention period of 1 to 10 minutes. The length of the effect of procedures to raise venous flow velocity cannot be determined by clinical trials. To apply mathematical techniques to estimate how long mechanical thromboembolism prophylaxis procedures will increase venous flow rate. Methods: In the survey, we examined 25 persons (poststroke patients), with an average age of 57.2±6.3 years. Regarding the proportion of genders, 13 (52%) participants were male and 12 (48%) female. The peak venous blood flow velocity was measured with a HADECO BIDOP ES-100V II type Doppler ultrasound device, using an 8MHz head, in the femoral vein, at the level of the hip joint. We estimated the change of the venous blood flow velocity from the available sampled data using the method of least squares. For the calculations, we used Microsoft Excel, version Mac Excel 2019.The decrease in peak venous flow velocity can be approximated by a logarithm function. Mathematical calculations show that after active thromboembolic prophylaxis interventions, resting venous flow velocity is restored at 26.8 minutes on the intact limb and 85.1 minutes on the hemiparetic side. Resting flow velocity is restored in 131.9 minutes after passive mobilization of the hemiparetic side and in 137.7 minutes after the consensual effect. Discussion: An elementary mathematical function can be used to estimate the time to recovery of peak venous flow velocity to resting state from measurements taken 15 minutes after the intervention. Active and passive mechanical thromboembolic prophylaxis after the intervention has a longer-term effect on venous flow velocity.